Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1590/1414-431x20142983
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Ginkgo biloba extract on insulin signaling cascade, dyslipidemia, and body adiposity of diet-induced obese rats

Abstract: Ginkgo biloba extract (GbE) has been indicated as an efficient medicine for the treatment of diabetes mellitus type 2. It remains unclear if its effects are due to an improvement of the insulin signaling cascade, especially in obese subjects. The aim of the present study was to evaluate the effect of GbE on insulin tolerance, food intake, body adiposity, lipid profile, fasting insulin, and muscle levels of insulin receptor substrate 1 (IRS-1), protein tyrosine phosphatase 1B (PTP-1B), and protein kinase B (Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 33 publications
7
45
0
2
Order By: Relevance
“…Significantly, chronic HFD-induced inflammation is now considered as a major factor in the onset of many metabolic disorders including obesity, T2DM, cardiovascular disease and some forms of cancer (Egger 2012; Hotamisligil 2006; Terzić, et al). Furthermore, HFD is known to alter the expression of genes involved in metabolic signaling and thus, impair normal metabolic function throughout the body (Banin, et al 2014; Choi, et al 2013). …”
Section: Nutrients and The Regulation Of Metabolic Homeostasismentioning
confidence: 99%
“…Significantly, chronic HFD-induced inflammation is now considered as a major factor in the onset of many metabolic disorders including obesity, T2DM, cardiovascular disease and some forms of cancer (Egger 2012; Hotamisligil 2006; Terzić, et al). Furthermore, HFD is known to alter the expression of genes involved in metabolic signaling and thus, impair normal metabolic function throughout the body (Banin, et al 2014; Choi, et al 2013). …”
Section: Nutrients and The Regulation Of Metabolic Homeostasismentioning
confidence: 99%
“…Rats in the NC and DM groups were administered intragastrically with the same amount of 0.5% carboxymethyl cellulose. At weeks 0, 4 and 8 following induction, fasting and 2 h postprandial blood glucose were measured using the glucose oxidase method on the Beckman Glucose Analyzer II (Beckman Coulter, Inc., Brea, CA, USA) and plasma INS levels were determined using an RIA Assay system (Linco Research, Inc., St. Charles, MO, USA) (20) according to the manufacturer's protocol. Following 8 weeks of different treatments, total RNA was isolated from rat pancreas tissues using TRIzol reagent (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA), and proteins were extracted using radioimmunoprecipitation assay buffer (RIPA; Beyotime Institute of Biotechnology, Haimen, China) for western blot analysis.…”
Section: Animalsmentioning
confidence: 99%
“…ere were a series of studies for hypertension in China, which suggested that dyslipidemia was one of risk factors of hypertension, and hyperlipidemia was associated with increased risk of hypertension [54][55][56][57]. e main effects of lowering blood lipids of GBE were sourced from flavonoids which could improve blood lipids through antioxidant effect and blood pressure reductions were achieved then [58][59][60][61]. In our study, there were some trials that reported two outcomes on blood lipids which were TC and TG.…”
Section: Findings and Interpretationsmentioning
confidence: 67%